English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

show work plaese thank you

2006-11-30 10:09:54 · 7 answers · asked by n 1 in Science & Mathematics Mathematics

7 answers

y=6

3(y+4)=5y
3y+12=5y
12=2y
y=6

2006-11-30 10:11:50 · answer #1 · answered by ? 2 · 1 0

Expand
3y+12=5y

Therfore:
12=5y-3y

12=2y
y=6

2006-11-30 13:31:29 · answer #2 · answered by lulu 3 · 0 0

3 (y+4) = 5y

3y +12 = 5y

12 = 2y

6=y

2006-11-30 10:58:40 · answer #3 · answered by Lisa C 1 · 0 0

3(y+4)=5y
3y+12=5y
12=2y
y=6

2006-11-30 10:13:55 · answer #4 · answered by Steven 2 · 0 0

3y + 12 = 5y
12 = 2y
y = 6

2006-11-30 10:12:00 · answer #5 · answered by Anonymous · 0 0

3 (y+4) = 5y
3y +12 = 5y
12 = 2y
6=y

2006-11-30 10:13:02 · answer #6 · answered by mainwoolly 6 · 0 0

3y +12 = 5y
12 = 5y -3y
12 = 2y
6 = y

2006-11-30 10:12:19 · answer #7 · answered by GreenFingers2000 2 · 0 0

fedest.com, questions and answers